2014
DOI: 10.3892/mco.2014.264
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ribonucleoside reductase subunit M1, but not excision repair cross-complementation group 1, is predictive in muscle-invasive bladder cancer treated with chemotherapy and radiation

Abstract: Abstract. The aim of this study was to determine the prognostic and predictive values of ribonucleoside reductase subunit M1 (RRM1) and excision repair cross-complementation group 1 (ERCC1) expression in patients with muscle-invasive bladder cancer treated with chemoradiotherapy. The expression of RRM1 and ERCC1 in pretreatment tumor samples of retrospectively identified patients was determined by immunohistochemical analysis. A total of 39 patients were included in this study; 49% were treated with neoadjuvan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…These conflicting data may result from differences in study population and methods for evaluating biomarkers. Similar with our results, Shilkrut et al [ 17 ] recently reported that the expression of RRM1, but not ERCC1, may predict response to gemcitabine-based chemoradiotherapy and worse cancer-specific survival in patients with muscle-invasive UC. They suggested that low RRM1 expression may help identify patients suitable for gemcitabine-based chemoradiotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…These conflicting data may result from differences in study population and methods for evaluating biomarkers. Similar with our results, Shilkrut et al [ 17 ] recently reported that the expression of RRM1, but not ERCC1, may predict response to gemcitabine-based chemoradiotherapy and worse cancer-specific survival in patients with muscle-invasive UC. They suggested that low RRM1 expression may help identify patients suitable for gemcitabine-based chemoradiotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…There are preclinical and clinical data indicating that high RRM1 protein levels in various cancers are associated with gemcitabine resistance [13, 14]. Moreover, several clinical studies have demonstrated the association between elevated RRM1 levels and unfavourable clinical outcomes in advanced bladder tumour patients treated with gemcitabine­based therapy [9, 15]. However, the relationship between RRM1 mRNA level and gemcitabine activity in NMIBC has not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, low expression of the ERCC1 protein will result in a longer OS after neoadjuvant therapy. 10 , 40 However, with detecting other ERCC1 and XPD polymorphisms, we were unable to discriminate between shorter OS and longer OS. Similarly, no differences were detected in the subgroup analyzes.…”
Section: Discussionmentioning
confidence: 66%